THE EFFECTS OF PUBLIC PARTICIPATION ON ENVIRONMENTAL IMPACT ASSESSMENT (The Pretoria Student Law Review, 2021)
With this research, I aim to address the practical aspect of legal compliance most major industry companies struggle to obtain. In South Africa, there seems to be an issue relating to legal compliance of environmental authorisations given by the Department of Environmental Affairs and Tourism (DEAT). Companies, specifically those companies which have a significant impact on the nonrenewable resources, are burdened with legal requirements that cannot be met, whether it be unreasonable or practically impossible to obtain. With every project undertaken by these companies an Environmental Management Plan (EMP) must be issued (by the company itself) outlining the expectations and limitations of the proposed project through an Environmental Impact Assessment (EIA) that clearly summarises the intended development and its impact. Should the EMP be accepted by the Regional Manager, a Scoping Report will be provided, by the applicant, clearly outlining the legal requirements and limitations placed on the proposed project. These conditions are mostly vague, as to what is expected or uncertain of how it should be achieved
Keywords: legal compliance; major industry companies; environmental authorisations; nonrenewable resources; Environmental Management Plan; Environmental Impact Assessment